Cost Effectiveness Analysis of Azithromycin and Doxycycline for Chlamydia Trachomatis Infection in Women: A Canadian Perspective - Fawziah Marra; Carlo A Marra; David M Patrick (Canadian Journal of Infectious Diseases)
OBJECTIVE: To assess the cost effectiveness of azithromycin versus doxycycline therapy for cervical Chlamydia trachomatis infections in Canada.